Factors Affecting Student Achievement in Faculty of Economics "X" University - Suhaily, Lily; Soelasih, Yasintha (Journal the Winners: Economics, Business, Management, and Information System Journal, 2015)
Education is an important point for many countries, including Indonesia. People with high education inÂ a country could make the country wealthier. Parents are usually aware that it is important for their children toÂ be educated. If the children are well educated, they will increase the standard of living of their parents and theirÂ selves. Based on this phenomenon, research evaluated factors that influence student achievement and alsoÂ evaluated the difference of achievement between students who are active in campus activities and are not active.Â A number of 329 questionnaires were distributed to Faculty of Economics, â€œXâ€ University students usingÂ random sampling. The result shows that the students themselves as factor that could determine theirÂ achievement. The evaluation also found that the achievement of student who is active in campus activities isÂ different with the achievement of student who is not active in campus activities.